Advances in hydrophilic nanomaterials for glycoproteomics. Issue 70 (15th August 2019) - Sun, Nianrong; Wu, Hao; Chen, Hemei; Shen, Xizhong; Deng, Chunhui
Abstract : In this article, the syntheses and applications of hydrophilic nanomaterials in glycoproteomics are reviewed. Abstract : Owing to the formidable challenge posed by microheterogeneities in glycosylation sites, macroheterogeneity of the modification number of glycans, and low abundance and ionization efficiency of glycosylation, the crucial premise for conducting in-depth profiling of the glycoproteome is to develop highly efficient technology for separation and enrichment. The appearance of hydrophilic interaction chromatography (HILIC) has considerably accelerated the progress in glycoproteomics. In particular, additional hydrophilic nanomaterials have been developed for glycoproteomics research in the recent years. In this review, we mainly summarize the recent progresses made in the design and synthesis of different hydrophilic nanomaterials, as well as their applications in glycoproteomics, according to the classification of the main hydrophilic functional molecules on the surface. Further, we briefly illustrate the potential retention mechanism of the HILIC mode and discuss the limits and barriers of hydrophilic nanomaterials in glycoproteomics, as well as propose their possible development trends in the future.